Extended Exergy Accounting for Karachi. (June 2016) - Jahangir, Soomro; Chen, Bin; Wakeel, Muhammad
Abstract: Exergy is stepping stone for thermos-economic analyses of complex system. In this paper, we presented an exergy-based resources accounting framework for urban systems. The cumulated exergy consumption in transformations of various resources and energy are presented in details. A case study of Karachi in Pakistan was conducted, in which the main energy supplier is found to be natural gas, followed by coal, nuclear Power and petroleum. The fluxes of labor and capital were also quantified by the exergy metrics, showing that the labor force input to Karachi is twice as much as that of the economy in context of the whole societal system.